Mortality from causes amenable and non-amenable to medical care: the experience of eastern Europe. Issue 6807 (12th October 1991) - Boys, R J; Forster, D P; Józan, P
Abstract : OBJECTIVE–To investigate comparative national trends in mortality from conditions amenable to timely, appropriate medical care and from those considered not to be amenable to such care. DESIGN–Analysis of trends in direct age standardised mortality from the 1950s to 1987. SETTING–Four eastern European nations (Hungary, Czechoslovakia, Poland, the German Democratic Republic) and two western European (the Federal Republic of Germany and England and Wales) and two North American nations (United States and Canada). SUBJECTS–The total populations of the relevant countries during the period examined. MAIN OUTCOME MEASURES–Proportional changes over time in age standardised mortality. Mortality from amenable and non-amenable causes was restricted to the age group 0-64. RESULTS–A divergence in the trends for all cause mortality between eastern Europe and the western nations occurred in about 1970, when the rates in western countries steadily declined but those in eastern Europe remained fairly static. In the age group 0-64 mortality from causes considered amenable to medical care fell less quickly in eastern Europe than in the West, particularly after 1970. In the same age group, mortality from non-amenable causes rose in eastern European countries from the late 1960s compared with substantial declines in such mortality in the West. CONCLUSIONS–Non-amenable causes of death seem to be the principal, but not exclusive, reason for lack of improvement in trends in all cause mortality in eastern Europe from 1970. The agenda for action in eastern Europe should give priority to a healthier lifestyle and improvement of the environment though not neglect enhancements in the quality and efficiency of direct health services.